Educational Quality as a Common Good - Gutiérrez-González, Manuel Alejandro; Ávila-Valdez, José Luis; Mejía-Toiber, Jana Aylim (CIAN-Revista de Historia de las Universidades, 2025)
UNESCO proposes to consider educational institutions from the perspective of the common good. To this end, the qualities derived from the collective memory, the integral educational relationship and the research relationship in a higher education institution were analyzed and, with this, the educational and research quality was addressed. In this cross-sectional study, a probabilistic method was used to obtain a sample of 1025 members of the Technological University of Queretaro (UTEQ). For this model, the concept of the common good was operationalized through a scale consisting of 76 items that measure the following dimensions: agency, stability, governance, justice and humanity. The educational community delineated the way in which common goods occur, thus describing its dynamics, indicating that there is no dimension that systematically shows a low collective perception. Particularities are pointed out that could be improved through actions or decision-making.